The Molecular Engineering of an Anti-Idiotypic Antibody for Pharmacokinetic Analysis of a Fully Human Anti-Infective - Lim, She Yah; Chan, Conrad E. Z.; Lisowska, Malgorzata M.; Hanson, Brendon J.; MacAry, Paul A. (PloS one, 2015)
Anti-idiotype monoclonal antibodies represent a class of reagents that are potentially optimal for analyzing the pharmacokinetics of fully human, anti-infective antibodies that have been developed as therapeutic candidates. This is particularly important where direct pathogen binding assays are complicated by requirements for biosafety level III or IV for pathogen handling. In this study, we describe the development of a recombinant, anti-idiotype monoclonal antibody termed E1 for the detection of a fully human, serotype-specific, therapeutic antibody candidate for the BSLIII pathogen Dengue virus termed 14c10 hG1. E1 was generated by naïve human Fab phage library panning technology and subsequently engineered as a monoclonal antibody. We show that E1 is highly specific for the fully-folded form of 14c10 hG1 and can be employed for the detection of this antibody in healthy human subjects' serum by enzyme linked immunosorbent assay. In addition, we show that E1 is capable of blocking the binding of 14c10 hG1 to dengue virus serotype 1. Finally, we show that E1 can detect 14c10 hG1 in mouse serum after the administration of the therapeutic antibody in vivo. E1 represents an important new form of ancillary reagent that can be utilized in the clinical development of a therapeutic human antibody candidate.